Community Service Reports: Animal Health Education, Service, and Prevention of Helminthiasis in Livestock Based on Herbal Areca catechu in Desa Bodag, Kare, Madiun - Asih Rahayu; Yos Adi Prakoso; Bagus Uda Palgunadi (Universitas Muhammadiyah Sidoarjo, 2023)
Desa Bodag, Madiun, has a large livestock population. The increase in the livestock population needs to be compensated by good management. Furthermore, this village has much areca nut (Areca catechu) production that needs to be put to good use. This community service aimed to educate, give service and promote the increase of utilization of areca nut as an anthelmintic agent in livestock. The community service was conducted in three ways: animal health education, animal health service, and educate regarding the utilization of areca nut as an anthelminthic agent. Based on the community service that has been conducted, there is 48 livestock in a single area of a farmer, consisting of 56.25% goats and 43.75% cattle. A lot of them were suffering from diseases, including helminthiasis. Based on the data, community education was performed to educate farmers about good animal health management and helminthiasis prevention using areca nuts. Animal health service was also performed in this society to mitigate livestock diseases. The community of Desa Bodag shows enthusiasm during all the community services programs, and they follow all the guidance. It is also concluded that community service in Desa Bodag has been successfully implemented. Highlights : Implementation of areca nuts as a natural anthelmintic agent, enhancing sustainable livestock health management. Focused community education on animal health and disease prevention, particularly targeting helminthiasis in livestock. Successful community engagement and adoption of new practices, demonstrating effective community service outcomes in Desa Bodag. Keywords : Livestock Management, Areca Nut, Anthelmintic Agent, Helminthiasis Prevention, Community Education